STUDY OF COMPETENCY MAPPING OF EX- SERVICEMEN OF INDIAN ARMY WORKING IN SERVICE SECTOR - Dhaka, Suresh Kumar; Singh, Archana; Goyal, Shikha (International Journal of Psychosocial Rehabilitation, 2020)
In the digital era, today organizations are facing the challenges to keep up its competency level to prove the quote “survival of the fittest”. For better human resource management, organizations need greater number of highly competent employees. Competent employees not only describe what is known by an employee about his effective job performance but also what and how they perform the job according to the attained competencies. The need of competency mapping arises which is vital not only for the general public but also for the ex-servicemen of Indian Army. This paper identifies the generic competencies in terms of knowledge, skill, ability and attitude some army personnel must possess or obtain in order to become multitasking in a particular job context. A qualitative as well as quantitative research was conducted for the identification of the gaps existing in acquired generic competencies of ex- servicemen in Indian Army and required generic competencies in service sector of India, so as to bridge the gap for the smooth transitions.